Residue-free alkali-treated aluminum foil for water disinfection: A novel supernatant Mg(OH)2 fabrication method - Ihsan, Taufiq; Novia, Fanny; Tetra, Olly Norita (Communications in Science and Technology, 2025)
This study presents a novel approach to fabricate alkali-treated aluminum (ATA) foil for point-of-use (POU) water disinfection, addressing the residue issue associated with conventional production methods. Traditional ATA foil production leaves a residual layer that hinders practicality in use. To cope with it, a supernatant Mg(OH)2 solution was employed, resulting in residue-free ATA foil. Two variants, conventional ATA foil (ATA foil-1) and supernatant-treated ATA foil (ATA foil-2), were fabricated and analyzed. Surface characterization revealed that ATA foil-2 had a smoother surface with fewer cracks while maintaining E. coli removal efficiency and methyl orange adsorption capacity similar as ATA foil-1. Maximum E. coli adsorption capacities were found at 572,967 CFU/cm2 for ATA foil-1 and 561,513 CFU/cm2 for ATA foil-2. Both foils achieved over 84% methyl orange removal, indicating adsorption as the primary removal mechanism. The findings demonstrated that the supernatant Mg(OH)2 method successfully produced residue-free ATA foil with comparable disinfection performance, thus eliminating the need for a washing step and enhancing its suitability for point-of-use water treatment applications.